1998
DOI: 10.1063/1.122303
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of avalanche breakdown for epitaxial diodes in 4H silicon carbide

Abstract: The temperature dependence of avalanche breakdown is investigated for uniform and microplasma-related breakdown in epitaxial 4H SiC p-n junctions. P-n mesa diodes fabricated with positive angle beveling and oxide passivation can withstand temperatures of up to 300–400 °C in the breakdown regime. Uniform avalanche breakdown in 4H silicon carbide appears to have a positive temperature coefficient, in contrast to the 6H polytype, where the temperature coefficient is negative. The influence of deep levels on avala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 9 publications
1
9
0
3
Order By: Relevance
“…Secondly, Zener tunneling is ruled out because the dark current increases with temperature as shown in Figure 5b, while Zener tunneling current decreases with increasing temperature 44 . Finally, the impact ionization is attributed to the multiplication while no microplasma avalanche or premature avalanche are observed as the EQE decreases with temperature, especially under high bias as shown in Figure 5c 44,45 . In PSS APDs, although phonon scattering has been greatly reduced compared with conventional HJ APD, the rudimental scattering still holds impacts on the multiplication performance.…”
Section: Device Performancementioning
confidence: 95%
“…Secondly, Zener tunneling is ruled out because the dark current increases with temperature as shown in Figure 5b, while Zener tunneling current decreases with increasing temperature 44 . Finally, the impact ionization is attributed to the multiplication while no microplasma avalanche or premature avalanche are observed as the EQE decreases with temperature, especially under high bias as shown in Figure 5c 44,45 . In PSS APDs, although phonon scattering has been greatly reduced compared with conventional HJ APD, the rudimental scattering still holds impacts on the multiplication performance.…”
Section: Device Performancementioning
confidence: 95%
“…Many researchers have reported that the temperature coefficient of V BD for 4H-SiC devices is positive. [25][26][27][28] From Ref.…”
Section: Influence Of Different Temperature Coefficientsmentioning
confidence: 99%
“…Построенная таким способом ВАХ уже не будет изотермической, поскольку во время пропускания лавинного импульса происходит сильный разогрев базовой области диода. Поскольку 4H-SiC p + −n 0 -переходы имеют положительный температурный коэффициент напряжения пробоя [7][8][9], кривая 2 на рис. 5 выглядит как S-образная.…”
Section: неизотермическая вахunclassified